RESULTS OF LAPAROSCOPIC THORACIC-ABDOMINAL SURGERY TO REPLACE THE ESOPHAGUS WITH THE STOMACH TO TREAT CANCER OF THE LOWER 2/3 ESOPHAGUS AT MILITARY HOSPITAL 175 - Trinh Van , Thao; Nguyen Van , Manh; Truong Duc, Cuong; Nguyen Phu , Thong; Doan Ngoc , Giao (Tạp chí Y Dược Thực hành 175, 2024)
Objective: To evaluate the effectiveness and safety of laparoscopic thoracic-abdominal esophagectomy and create a replacement gastric tube in the treatment of lower 2/3 esophageal cancer at Military Hospital 175 Subjects and methods: A prospective study, cross-sectional description of 34 cases of lower 2/3 esophageal cancer undergoing laparoscopic thoracoabdominal esophagectomy and creating a replacement gastric tube at Military Hospital175 from July 2015 to March 2022. Initially, technical support was provided by Cho Ray Hospital. Results: All patients were male; the mean age was 55.2 ± 10.2 (28-79) years, 76.5% with a history of smoking and drinking alcohol. Cancer was located in the lower third of the esophagus in 58.8% of cases, middle third accounted for 41.2%. All cases (100%) were squamous cell carcinoma. According to AJCC 8th edition, the disease stages were stages II, III, and IV at rates of 50%, 47.1%, and 2.9% respectively. The ratio of successful surgery was 100%. The average duration of surgery was 387.4 ± 69.6 minutes, of which the thoracic phase was 174.9 ± 61.6 minutes, the abdominal phase was 150.3 ± 34.9 minutes, and the cervical phase was 62.2 ± 22.3 minutes. Complications in operation accounted for 14.7% of cases and were all managed successfully. The postoperative complication rate was 44.1%, including pneumonia was 14.7%, hoarseness was 35.3%, collapsed lung 5.9%, anastomotic leak was 5.9%, and and no mortality (0%). Quality of life after surgery: good 58.6%, average 31.0%, poor 10.3%. The average survival time after surgery was 25.5 ± 2.5 months, one year 77.4%, two years 56.7%, three years 24.3%. Conclusions: Laparoscopic thoracoabdominal esophagectomy and the creation of a replacement gastric tube were successfully performed at Military Hospital 175 with a favorable complication rate, survival time, and significantly improved quality of life.